Characteristics and Incidence of Colon Complication in Necrotizing pancreatitis: A Propensity Score-Matched Study - Lu J; Zheng Z; Ding Y; Qu Y; Mei W; Fang Z; Qu C; Feng Y; Guo Y; Gao C; Cao F; Li F (Dove Medical Press, 2023)
Jiongdi Lu,1,2,* Zhi Zheng,3,* Yixuan Ding,1,2 Yuanxu Qu,1,2 Wentong Mei,1,2 Zhen Fang,1,2 Chang Qu,1,2,* Yulu Feng,4 Yulin Guo,1,2 Chongchong Gao,1,2 Feng Cao,1,2 Fei Li1,2 1Clinical Center of Acute Pancreatitis, Capital Medical University, Beijing, People's Republic of China; 2Department of General Surgery, Xuanwu Hospital, Capital Medical University, Beijing, People's Republic of China; 3Department of General Surgery, Beijing Friendship Hospital, Capital Medical University, Beijing, People's Republic of China; 4Chui Yang Liu Hospital Affiliated Tsinghua University, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Fei Li, Clinical Center of Acute Pancreatitis, Department of General Surgery, Department of Surgery, Xuanwu Hospital of Capital Medical University, No. 45, Changchun Street, Xicheng District, Beijing, 100053, People's Republic of China, Tel +86-10-83198731, Fax +86-10-83198868, Email feili36@ccmu.edu.cn Feng Cao, Clinical Center of Acute Pancreatitis, Department of General Surgery, Xuanwu Hospital of Capital Medical University, No. 45, Changchun Street, Xicheng District, Beijing, 100053, People's Republic of China, Email f.cao@xwhosp.orgObjective: To clarify the incidence of colonic complications in patients with NP and their impact on prognosis.Methods: The clinical data of NP patients admitted to the Department of General Surgery of Xuanwu Hospital, Capital Medical University from January 2014 to December 2020 were retrospectively analyzed. Patients were grouped according to the presence or absence of colonic complications, and the clinical prognosis of the two groups was analyzed after matching using a 1:1 propensity score, The primary study endpoint was patient mortality during hospitalization. Data are reported as median (range) or percentage of patients (%).Results: A total of 306 patients with NP were included in this study, and the incidence of colonic complications was 12.4%, including 15 cases of colonic obstruction, 17 cases of colonic fistula, and 9 cases of colonic hemorrhage. Before matching, patients in the colonic group had severe admissions and poor clinical outcomes (P< 0.05). After matching, the baseline data and clinical characteristics at admission were comparable between the two groups of patients. In terms of clinical outcomes, although the mortality was similar in the two groups (P> 0.05), but patients in the colonic group were more likely to have multiorgan failure, length of nutrition support, number of minimally invasive interventions, number of extra-pancreatic infections, length of ICU stay and total length of stay were significantly higher than those of patients in the group without colonic complications (P< 0.05). During long-term follow-up, patients in the colonic group were more likely to develop recurrent pancreatitis.Conclusion: About 12.4% of NP patients developed colonic complications, and after PSM it was found that colonic complications only led to a longer hospital stay and an increased number of clinical interventions in NP patients and did not increase the mortality.Keywords: necrotizing pancreatitis, colon involvement, propensity score match